Assessing Frontal Lobe Function on Verbal Fluency and Emotion Recall in Autism Spectrum Disorder by fNIRS. - Chien, Yi-Ling; Tseng, Yi-Li; Tsai, Wen-Che; Chiu, Yen-Nan (Journal of Autism & Developmental Disorders, 2025)
This study applied the functional near-infrared spectroscopy (fNIRS) to investigate frontal activity in autism when performing verbal fluency test and emotion recall task. We recruited 32 autistic adults without intellectual disability and 30 typically-developing controls (TDC). Prefrontal hemodynamic changes were evaluated by fNIRS when the participants performed the verbal fluency test and emotion recall task. fNIRS signals in the prefrontal cortex were compared between autism and TDC. Compared to TDC, autistic adults showed comparable performance on the verbal fluency test but exhibited lower frontal activity on the vegetable category. In the verbal fluency test, left frontal activity in TDC significantly increased in the vegetable category (vs. fruit category). In the emotion recall task, left frontal activity increased significantly in TDC when recalling emotional (vs. neutral) events. This increase of left frontal activity on the more difficult works was not found in autism. Similarly, brain activities were related to test performance only in TDC but not in autism. In addition, more severe social deficits were associated with lower frontal activity when recalling emotional events, independent of autism diagnosis. Findings suggested reduced frontal activity in autism, as compared to TDC, when performing verbal fluency tests. The reduction of left frontal activation in verbal fluency test and emotion recall tasks might reflect on the social deficits of the individual. The fNIRS may potentially be applied in assessing frontal lobe function in autism and social deficits in general population. Trial registration number: NCT04010409. Lay Summary: Cognitively able autistic adults showed lower prefrontal activation than non-autistic people on the verbal fluency task that assesses executive function. Although higher cognitive load typically triggers stronger prefrontal activity in verbal fluency and emotion recall tasks, this task-difficulty effect was not found in autistic adults. In addition, more severe social deficits were independently associated with lower frontal activity when recalling emotional events, implying a potential utility of the fNIRS in assessing frontal lobe function in autism and for social deficits in general population.